Principles in power: Latin America and the politics of U.S. human rights diplomacy - Walker, Vanessa (The United States in the world, 2020)
Introduction : Principles in Power -- The Chilean Catalyst : Cold War Allies and Human Rights in the Western Hemisphere -- Words Are Not Enough : Building a New Human Rights Agenda in the Shadow of the Past -- A Special Responsibility : Human Rights and U.S.-Chilean Relations -- One of the Most Difficult and Vexing Cases : Weighing the Costs of Human Rights in U.S.-Argentine Relations -- The Reagan Reinvention : A Cold War Human Rights Vision -- Conclusion : The Golden Years of Human Rights?